Faculty Engagement as a Strategic Driver of Institutional Performance in Higher Education - Dhanraj Kongle; Ulfath Begum Syeda; Shifa Saba (Involvement International Journal of Business, 2025)
Faculty engagement is increasingly recognized as a determinant of academic excellence in higher education institutions. This study investigates the impact of faculty engagement on perceived academic quality at Avinash Group of Institutions, Hyderabad, India, with a focus on factors such as job satisfaction, personal and career growth, and institutional support. A descriptive design using a mixed-methods approach was adopted. Primary data were collected from 47 faculty members (10% of the population) through a structured questionnaire using convenience sampling. Quantitative analysis was conducted using descriptive statistics, correlation, regression, and two-way ANOVA in MS Excel, while qualitative analysis explored additional factors influencing academic excellence. The findings reveal that 81% of respondents agreed faculty engagement significantly impacts academic excellence. Regression analysis identified personal and career growth as the strongest predictor (β = 0.651), followed by job satisfaction (β = 0.401) and innovative teaching, collaboration, and institutional support (β = 0.397). ANOVA confirmed job satisfaction as highly significant (F = 28.23, p < 0.001), whereas years of experience (F = 0.976, p = 0.5038) and its interaction with job satisfaction (F = 0.7527, p = 0.8423) were not significant. Qualitative findings suggested leadership style, student discipline, infrastructure, and research opportunities as additional contributors to academic excellence. The results align with previous studies that emphasize the role of personal and professional growth, job satisfaction, and innovative teaching in enhancing academic performance. The study also underlines the importance of institutional support systems, work-life balance, and recognition mechanisms in sustaining engagement. However, limitations include reliance on self-reported data, a small and non-random sample, and the exclusion of student and management perspectives.